Inventory of the Woody flora of Jammu University Campus, Jammu & Kashmir, India (International Journal of Food and Nutritional Sciences, 2022)
In an attempt to reveal the diversity, status and composition of woody plant species, surveys were conducted in the Jammu University campus. The results indicate that the total number of woody plants in the campus include 225 species belonging to 176 genera and 76 families. Of which, 211 woody species distributed among 166 genera are represented by Angiosperms while 14 woody species belonging to 10 genera are of Gymnosperms. The flowering plants have been found to be dominant, indicating their potential to withstand less rainfall and high temperature in the campus. The present study reveals that Fabaceae